The long and short-run spatial impacts of trade - MA, Lin (Institutional Knowledge at Singapore Management University, 2024)
We explore how the spatial impacts of trade evolve over time using a dynamic spatial model that incorporates capital accumulation and skill acquisition. We show that in the short run, the spatial impacts of trade mainly depend on the initial conditions, especially the endowments of physical and human capital across locations. However, in the long run, trade shocks shape the distribution of production factors across space through factor accumulation and migration, resulting in significantly different spatial impacts. In the context of China’s WTO accession, we find that international trade is seven times more effective in driving the population towards coastal areas in the long run than in the short run. The skill composition of trade-induced migration exhibits a reversal over time. Furthermore, we demonstrate that policies designed to alleviate the localized impacts of globalization would be misdirected and underfunded if policymakers overlook the intertemporal variations in the spatial impacts of trade.